Analisis Pengelolaan Limbah Tahu di Kecamatan Adiwerna Kabupaten Tegal - M.Rizki Arif Rahman Hakim; Priyatno Harsasto; Wiwik Widayati (Journal of Politic and Government Studies, 2015)
One of the issues that must be considered in the study population are enviromental problems. Increasing number of people will have implications for the more challenging enviromental problems. Of various problems concerning enviromental health in the society, along with the many cases of waste management are detrimental to society and the enviromental. Waste pollution cases occur in many large cities, one in Tegal regency.Tegal district is the center of industry, including industrial centers are located in the district know Adiwerna. Knowing the typical food Tegal regency. Many craftsmen know in the district Adiwerna impact also on the quality of waste management know, because managemant waste know who carried out in the district entrepreneurs Adiwerna very doubt about. So that existence of questionable enviromental agencies and ultimately the role and function of enviromental oversight is not optimal. The background of the problem arises of how the analysis of waste management tahu, and how supervision by government enviromental agencies, especially in deadling with waste management knows and enviromental oversight funciton in waste. Method management research is a qualitative research method is descriptive with data collection techniques include observation, interview and literature. Waste managementin the district know Adiwerna experiencing various problems so that the implementation of waste management tofu. In the district Adiwerna not optimal. There are several factors that cause is not optimal waste management in the district tofuAdiwerna. These factors include inadequate waste management oversight conduceted enviromental agencies, both preventive and represive control. So we need a new construction. Enhance the role and function of enviromental oversight in the management of Tegal regency waste know in the district adiwerna